2011
DOI: 10.1371/journal.pone.0024770
|View full text |Cite
|
Sign up to set email alerts
|

Clonal Population of Mycobacterium tuberculosis Strains Reside within Multiple Lung Cavities

Abstract: BackgroundUnsuccessful treatment outcomes among patients with multi-/extensively- drug resistant tuberculosis (TB) have hampered efforts involved in eradicating this disease. In order to better understand the etiology of this disease, we aimed to determine whether single or multiple strains of Mycobacterium tuberculosis (MTB) are localized within lung cavities of patients suffering from chronic progressive TB.Methodology/FindingsMultiple cavity isolates from lung of 5 patients who had undergone pulmonary resec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…An earlier study investigated different lesions obtained following lung surgery and found discrete pulmonary lesions carried strains with different drug-resistant mutations, which had evolved from a single parental strain 11 . This finding was further confirmed by analyzing the drug susceptibility profile of multiple cavity isolates from 5 patients that underwent pulmonary resection surgery 12 . In these situations, clonal interference does not apply because the strains reside in physically discrete lesions and genetic heteroresistance might therefore be a long-term phenomenon in vivo .…”
mentioning
confidence: 65%
“…An earlier study investigated different lesions obtained following lung surgery and found discrete pulmonary lesions carried strains with different drug-resistant mutations, which had evolved from a single parental strain 11 . This finding was further confirmed by analyzing the drug susceptibility profile of multiple cavity isolates from 5 patients that underwent pulmonary resection surgery 12 . In these situations, clonal interference does not apply because the strains reside in physically discrete lesions and genetic heteroresistance might therefore be a long-term phenomenon in vivo .…”
mentioning
confidence: 65%
“…The finding of isolates from different lesions in the same patient that have different resistance profiles (ie, heteroresistance), lends support to the hypothesis of differential drug penetration or exposure. 82 Collectively, these data from laboratory experiments, clinical trial simulations, and prospective clinical studies provide support for the notion that biological variability (eg, pharmacokinetic variability) is the main culprit for emergence of multidrug-resistant tuberculosis. Therefore, innovative and new methods are needed to optimally dose patients.…”
Section: Pathogenesis and Mechanisms Of Drug-resistant Tuberculosismentioning
confidence: 78%
“…In MDR cases, the tubercle bacilli are resistant to anti-TB drugs, which results in the chronic progressive disease with cavitation in the lungs of patients. 14 A previous study showed that the presence of pulmonary cavitation is linked to the development of drug resistance during treatment. 28 Therefore, the interaction between pulmonary cavitation and drug resistance may accelerate the generation and expansion of pulmonary cavitation.…”
Section: Discussionmentioning
confidence: 99%
“…14, 15 A study investigating the relationship between VNTR profiles and disease progression revealed that specific VNTR genotypes were associated with disease progression in Mycobacetrium avium pulmonary infection. 16 Similar results were observed by Shin et al 17 who showed that fibrocavitary diseases were more likely to be grouped into a particular cluster among Mycobacterium abscessus diseases.…”
Section: Introductionmentioning
confidence: 99%